Along the integral margin uneven development in a Myanmar squatter settlement - Campbell, Stephen (Anthropologist) (ILR Press, an imprint of Cornell University Press, 2022)
"This book is an ethnographic study of informal housing and labor among residents of a squatter settlement on the outskirts of Yangon, Myanmar's former capital, based on research conducted from 2016 to 2019"--